Social Impact Assessment Project on Cholangiocarcinoma Screening and Care Program - Aimimtham, Sukanya; Pakittawichit, Thananchakorn; Saiyasopon, Sukhumvit; Chamaratana, Thanapauge; Jearviriyaboonya, Jakkrich; Purnomo, Eko Priyo (Journal of Ecohumanism, 2024)
The research aims to assess users utility and cost-effectiveness based on the results of rapid antigen test kits for urine and abdominal ultrasound methods. This study uses qualitative methods to analyze liver fluke screening among individuals aged 40 and above in four provinces. Purposive sampling was used, with 373 participants and 379 participants, respectively. Utility measurement tools included a direct Visual Analog Scale (VAS) and indirect EuroQoL (5Q-5D-5L), and willingness to pay value was measured using bidding. The result shows that the sample group has an average VAS score of 76.90, with slight pain or discomfort reported in the five health dimensions. The utility value reflecting daily quality of life is 0.89. The average willingness to pay per use for rapid test kits and abdominal ultrasounds is 187 baht and 796 baht, respectively. Reasons for not paying higher include income factors, high prices, and personal limitations. However, participants believe public hospitals could support examination costs and provide access to benefits. The project benefits people economically, socially, and culturally, and if the Ministry of Public Health and related agencies can effectively use it, it will maximize benefits.